Telestroke activity across Europe; The results of a European Stroke Organization survey - Ryan, Daniel J.; Mueller-Barna, Peter; Von Martial, Rascha; Corea, Francesco; Zvan, Bojana; Zivanovic, Zeljko; Barlinn, Jesicaa; Krasinska-Chavez, Milena; Alasheev, Andrey (Frontiers in Stroke, 2024)
Introduction: Telestroke care is likely non-inferior to face-to-face care in acute stroke management while it also provides rural sites with access to specialist expertise. However, little is known about the distribution and activity of telestroke networks across Europe. Consequently, the European Stroke Organisation (ESO) Telestroke Committee aimed to address this through an online questionnaire. Methods: The questionnaire was developed through an unstructured consensus process, ratified by the ESO executive committee and emailed to ESO members. Results: Of 2147 ESO members contacted, complete datasets were submitted on 25 networks from ten countries. Among the 25 networks, the mean number of hubs per network was 1.6 (SD 1.2) and mean number of spokes was 9 (SD 6.7) with considerable variability observed (range 2-24 spokes/network). All sites used audiovisual communication. The mean telemedicine consultations per year per site was 197 (SD 164). The primary reason for consultation was "diagnostic and triage purposes" in all but one network. The median number of strokes per site was 175 (IQR 192) and the mean intervention rate was 12.3% (SD 10) (thrombolysis or thrombectomy). Conclusion: At 25 networks this survey probably under-represents telestroke activity across Europe yet it is still the first study to provide a continent-wide geographical footprint and report of activity within networks. There was considerable variability in network size and activity. Spoke sites reported an acceptable intervention rate of 12.3%. This compares favorably with national data from European countries, and suggests telestroke care supports reasonable intervention rates.